DETERMINASI RETURN SAHAM PADA PERUSAHAAN SUB-SEKTOR PERKEBUNAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Dasril, Yuki Dwi Darma; Pujiharta, Pujiharta (Jurnal Investasi, 2022)
To get optimal investment returns, of course, investors need to analyze based on financial ratios in the financial statements as indicators of investing decision. This type of research is explanatory which is useful in analyzing the relationship between one variable and another. The source of data used in this study is secondary data that is quantitative in nature with the determination of the sample used by the purposive sampling method and obtained 12 companies in the plantation sub-sector that were sampled in the study. The analytical method used is panel data regression analysis with pool data analysis. Based on the results of partial test, partially the CPO commodity price variable has a significant effect on stock returns, the profitability performance variable proxied using net profit margin has a significant effect on stock returns, the market performance variable proxied using the price earning ratio has no significant effect on stock returns. The performance of the leveraged leverage which is proxied using the debt to equity ratio has a significant effect on stock returns.